The three-dimensional arrangement of the mineralized collagen fibers in elephant ivory and its relation to mechanical and optical properties. (May 2018) - Albéric, M.; Gourrier, A.; Wagermaier, W.; Fratzl, P.; Reiche, I.
Graphical abstract: Abstract: Elephant tusks are composed of dentin or ivory, a hierarchical and composite biological material made of mineralized collagen fibers (MCF). The specific arrangement of the MCF is believed to be responsible for the optical and mechanical properties of the tusks. Especially the MCF organization likely contributes to the formation of the bright and dark checkerboard pattern observed on polished sections of tusks (Schreger pattern). Yet, the precise structural origin of this optical motif is still controversial. We hereby address this issue using complementary analytical methods (small and wide angle X-ray scattering, cross-polarized light microscopy and scanning electron microscopy) on elephant ivory samples and show that MCF orientation in ivory varies from the outer to the inner part of the tusk. An external cohesive layer of MCF with fiber direction perpendicular to the tusk axis wraps the mid-dentin region, where the MCF are oriented mainly along the tusk axis and arranged in a plywood-like structure with fiber orientations oscillating in a narrow angular range. This particular oscillating-plywood structure of the MCF and the birefringent properties of the collagen fibers, likely contribute to the emergence of the Schreger pattern, one of the most intriguing macroscopic optical patterns observed in mineralized tissues and of great importance for authentication issues in archeology and forensic sciences. Statement of Significance: Elephant tusks are intriguing biological materials as they are composed of dentin (ivory) like teeth but have mineralized collagen fibers (MCF) similarly arranged to the ones of lamellar bones and function as bones or antlers. Here, we showed that ivory has a graded structure with varying MCF orientations and that MCF of the mid-dentin are arranged in plywood like layers with fiber orientations oscillating in a narrow angular range around the tusk axis. This organization of the MCF may contribute to ivory's mechanical properties and, together with the collagen fibers birefringence properties, strongly relates to its optical properties, i.e. the emergence of a macroscopic checkerboard pattern, well known as the Schreger pattern.